'It is important for us to see the mentors as persons' – participant experiences of a rehabilitation group. Issue 1 (1st January 2019) - Andreasen, Josephine; Poulsen, Stig; Hoej, Michaela; Arnfred, Sidse
ABSTRACT: Purpose : The purpose of the study was to examine what was beneficial and what was challenging in a group intervention for young adults based on RENEW principles in a municipal employment centre. RENEW (Rehabilitation for Empowerment, Natural support, Education, and Work) is an education-oriented support model for young people. Method : The eight young adults who participated in the group and three mentors who led the group were interviewed about their experiences with the group, and a workshop was held for staff to validate the themes found in the study. Results : Three themes emerged, one denoted the importance of helpful personal relationships, both between the mentors and the young adults and among the young adults; another denoted how an authentic attitude from the mentors made group exercises inconspicuous as the group members experienced activities in the group as originating from spontaneous, genuine interest rather than the manual-based exercises they were. The last theme conveyed how the group process was challenged by the institutionally regulated compulsory attendance and the mentors' lack of teamwork resources . Conclusions : The study suggests that meeting young adults authentically and flexibly combining a certain element of self-disclosure with a manual-based group intervention such as RENEW can strengthen relatedness and convey hope, thereby supporting educational rehabilitation.